Comparison of soil mesofauna communities in protected forests and production forests of Pesanggrahan Beach, Malang Regency - Wanodya Tiara Raras; Rohman Fatchur; Rahayu Sofia Ery; Sumberartha I Wayan (BIO Web of Conferences, 2025)
Mesofauna soil plays an important role for balancing soil ecosystem and its abundance is influenced by soil environment. This study aims to reveal and compare soil mesofauna communities based on H', E, R, IVI, litter decomposition rate and the relationship of physico-chemical factors to the number of species and abundance of individuals in protected forest areas and production forests of Pesanggrahan Beach. In each forest type, 50 samples were taken at depths of 10 cm from the soil surface using line transect method, then soil samples were extracted using Barlese set method. The study found 44 species in protected forests and 37 species in production forests. The diversity index of soil mesofauna in protected forests was 3.134 (high), while production forests it was 2.971 (medium). The evenness index in both types of high forest, namely protected forest at 0.830 and production forest at 0.823. The richness index was, in protected forest at 6.082 and production forest at 5.714. The average decomposition rate in protected forests was 0.043 g/day, while production forests it was 0.025 g/day. Multiple linear regression tests showed that physico-chemical factors affect the abundance of individuals and the total number of mesofauna species.